(untitled) (Colloquia Comparativa Litterarum, 2025)
What we may call “public art” in Turkey starts with the establishment of the Turkish Republic itself. Mostly, it is associated with monuments and sculptures in public spaces in the modernising urban environment within the newly founded secular state that brought changes not only to the way of life and its dynamics, but also to the entire system of values and the aesthetics of space. The most popular public space, the square, altered completely its function and vision: from being entirely the domain of men enclosed between the mosque, the bazaar, and the coffee-house, to becoming the vital point of the new Europeanised Turkish cities highlighting thus the national identity and memory, and the new political order. This brief survey focuses on the different approaches to public spaces in Turkey and to public works of art, which are more than just ideological instruments of power. The study of this situation in a society that is concerned with its own identity appears as one of the most important issues of contemporary public art in Turkey. On the other hand, public art raises awareness about the value of art in public dialogue, and helps bring forward new interpretations and artistic quests.